Effects of magnetic field gradients on the aggregation dynamics of colloidal magnetic nanoparticles1. Issue 38 (14th October 2015) - Heinrich, D.; Goñi, A. R.; Osán, T. M.; Cerioni, L. M. C.; Smessaert, A.; Klapp, S. H. L.; Faraudo, J.; Pusiol, D. J.; Thomsen, C.
<x xml:space="preserve">Abstract</x> We combined theoretical models, experimental results and molecular dynamics simulations to explain the aggregation dynamics of ferrofluids in the presence of magnetic field gradients.